2021
DOI: 10.1111/ecaf.12471
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Italy's education‐related digital divide

Abstract: This article examines differences in home computer and internet access among Italian households between 2005 and 2016. The results indicate that while computer and internet penetration has increased across all educational levels and geographical areas, digital inequalities related to education still persist and are substantial, especially in the South. Additionally, the findings suggest that the digital gap at the bottom of the education distribution is widening over time. Access among households whose referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
2
0
4
Order By: Relevance
“…In fact, since complexity is an important barrier to technology adoption, people with a higher level of education seem to be more keen to overcome this type of problem [74,75]. For example, in Italy, a recent study confirmed that access to a computer and the internet at home increases with the educational level [76]. This could be the reason why in the Italian sample there are more educated individuals than in the German one (especially those having an upper secondary educational level).…”
Section: Study Limitationsmentioning
confidence: 99%
“…In fact, since complexity is an important barrier to technology adoption, people with a higher level of education seem to be more keen to overcome this type of problem [74,75]. For example, in Italy, a recent study confirmed that access to a computer and the internet at home increases with the educational level [76]. This could be the reason why in the Italian sample there are more educated individuals than in the German one (especially those having an upper secondary educational level).…”
Section: Study Limitationsmentioning
confidence: 99%
“…İnternetin ve teknolojik araçların kullanımı belirli düzeyde ekonomik sermaye gerektirdiği için bu araçlara sahipliğin ve bunların kullanımının bireylerin sosyal refah düzeylerinin bir göstergesi olarak kabul edilebileceği söylenebilir. Bununla ilintili olarak eğitim düzeyi yüksek ailelerin eğitim düzeyi düşük olan ailelere kıyasla dijital teknolojilere sahip olma olasılıkları daha yüksektir (Pietro, 2021). Ayrıca van Deursen ve van Dijk (2015) bireylerin eğitim düzeyleri yükseldikçe dijital becerilerinin arttığını belirtmişlerdir.…”
Section: Eğitimde Dijitalleşmenin Eğitimde Eşitsizlikler Açısından Ri...unclassified
“…Dijital eğitim süreçlerinde evlerinde bilgisayar ya da internet bağlantısı olmayan öğrenciler çevrimiçi öğrenme ortamlarına erişmek, derslere katılmak ya da ödevlerini teslim etmek konusunda yetersiz kalmaktadırlar. Bu da farklı sosyoekonomik arka planlardan gelen öğrenciler arasında eşitsizliğin artmasına yol açmaktadır (Pietro, 2021). Yoksul, eğitim düzeyi düşük, kırsal bölgelerde yaşayan ailelerin dezavantajlı konumlarından dolayı dijital olarak dışlanma olasılığı daha yüksektir (Pietro 2021) ve bu değişkenler öğrenciler arasında dijital eşitsizliklere yol açmaktadır (Sosa Díaz, 2021).…”
Section: Eğitimde Dijitalleşmenin Eğitimde Eşitsizlikler Açısından Ri...unclassified
See 1 more Smart Citation
“…Algunos estudios, resaltan el papel crítico que tiene el desarrollo de políticas educativas que promuevan de manera efectiva la accesibilidad tanto a los dispositivos digitales (computadores, portátiles, Tablet y Smartphones) como a la conectividad real y ancho de banda a Internet para los estudiantes (Kummitha et al, 2021). Asimismo, recientes investigaciones demuestran que existe una corrrelación de la existencia de la Brecha Digital entre las poblaciones que tienen mejores niveles de calidad en la educación, frente a las que sufren las consecuencias de las restricciones en accesibilidad real al mundo digital (Cabero y Valencia, 2020;Di Pietro, 2021). De tal modo que, las múltiples brechas relacionadas con las diferencias de acceso y participación efectiva en la educación, investigación y desarrollo del potencial cognitivo, no se resuelven solamente garantizando la tecnología digital, siendo necesario promover el desarrollo de la competencia digital, y democratizando la participación en los diferentes ámbitos constitutivos del conocimiento (Sunkel y Ullmann, 2019).…”
Section: Introductionunclassified